Strategi Kepala Sekolah dalam Meningkatkan Profesionalisme Guru di Sekolah Dasar Islam Terpadu - Nurul Affika Aulia; Mohammad Sofwan Effendi; Neti Karnati (Universitas Negeri Makassar, 2026)
Teacher professionalism is one of the key factors in determining the quality of learning in elementary schools, particularly in Integrated Islamic Elementary Schools (SDIT). As educational leaders, principals hold a strategic role in guiding, directing, and enhancing teacher competencies. This study aims to examine the strategies employed by principals to improve teacher professionalism based on previous literature. The method used is a literature review by analyzing books, journal articles, and relevant research findings. The results indicate that the principal’s main strategies include academic supervision, training and professional development, motivation, reward and sanction systems, strengthening collaboration, the utilization of technology, as well as the internalization of Islamic values in teacher development. In conclusion, principals need to implement these strategies consistently and contextually in accordance with the characteristics of integrated Islamic schools. This study is expected to serve as a reference for educational practitioners and future research.